Educational intervention to adopt selective laser trabeculoplasty as first-line glaucoma treatment: Randomized controlled trial: Educational intervention on selective laser trabeculoplasty. Issue 3 (May 2022) - Tran, Evelyn; Sanvicente, Carina; Hark, Lisa A; Myers, Jonathan S; Zhang, Qiang; Shiuey, Eric J; Tran, Judie; Bonafede, Lucas; Hamershock, Rose A; Withers, Colleen; Katz, L Jay
Purpose: To determine the efficacy of an educational intervention on patient adoption and attitudes toward selective laser trabeculoplasty (SLT) as first-line treatment for glaucoma. Methods: This study is a randomized controlled trial. Subjects include 33 patients within 1-year diagnosis of either primary open-angle glaucoma, ocular hypertension, or pseudoexfoliation syndrome. After informed consent, subjects were randomly assigned to a Usual Care or Educational Intervention group. All subjects completed a pre-intervention questionnaire. The Educational Intervention group was shown a slideshow presentation and a 3-min video and given a post-intervention questionnaire. Follow-up examinations were reviewed for 6 months to determine subject completion of SLT, the primary outcome. Secondary outcomes include assessment of attitude toward SLT before and after intervention. Results: Age, gender, and baseline characteristics between the groups did not differ. The Usual Care group had a higher proportion of African Americans (77% vs 31%, p  = 0.04). At 6 months following the intervention, 63% of subjects underwent SLT compared to 35% of Usual Care subjects ( p  = 0.12). Older age was associated with decreased SLT uptake (OR 0.90, 95% CI 0.82–0.99, p  = 0.03). Prior to the intervention, there were no differences in attitudes of both groups regarding SLT therapy. Nineteen percent of Educational Intervention subjects changed positively toward SLT ( p  = 0.08) and 50% scheduled an SLT appointment after intervention ( p  = 0.005). Conclusions: A slideshow and video-based educational intervention may positively enhance patient adoption of SLT. Clinical trial registration name, number, URL: Educational Intervention to Adopt SLT as First-Line Glaucoma Treatment, NCT03365778, https://clinicaltrials.gov/ct2/show/NCT03365778